Lithium polyhydrides synthesized under high pressure and high temperature. (18th July 2017) - Matsuoka, Takahiro; Kuno, Keiji; Ohta, Kenji; Sakata, Masafumi; Nakamoto, Yuki; Hirao, Naohisa; Ohishi, Yasuo; Shimizu, Katsuya; Kume, Tetsuji; Sasaki, Shigeo
Abstract : Polyhydrides of alkali metals under high pressures have been attracting great interests owing to the predicted pressure‐stabilized untraditional stoichiometries and potential superconductivity. We have performed Raman scattering measurements of lithium polyhydrides synthesized under high pressure and high temperature conditions up to 182 GPa. Between 30 and 180 GPa, four phases appear, and they are tentatively named α (30–140 GPa), β (30–90 GPa), γ (90–140 GPa), and δ (140 GPa) phase. By observing the H2 vibrons at higher wavenumbers than pure H2 and their pressure dependence, it was revealed that the α phase contains electrically neutral H2 in its crystal lattice without electron transfer from Li atoms. The comparisons with H2 ‐containing rare gas compounds Ar(H2 )2, Kr(H2 )4, and Xe(H2 )8 suggest that a H2 molecule is surrounded by six to eight neighboring H2 molecules in the α phase. On the other hand, the Raman spectra of the β, γ, and δ phases suggest that they contain the elongated H2 that is negatively charged by the electron transferred from the surrounding matrices. All the α, β, γ, and δ phases were found to remain transparent insulators at pressures below 182 GPa. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : The structural properties of four phases of lithium polyhydride LiH x (temporarily named α, β, γ, and δ phases) synthesized under high pressure and high temperatures were studied. Raman scattering measurements have revealed the presences of the electrically neutral H2 molecules in the crystal lattice of α phase, and the contained H2 is thought to have the eight or six nearest neighboring H2 in the unit cell. In the β, γ, and δ phases, the elongated H2 that are negatively charged by the electron transferred from surrounding matrices are possibly accommodated. All the α, β, γ, and δ phases remain transparent insulators up to 182 GPa.